2019
DOI: 10.3389/fnins.2019.00526
|View full text |Cite
|
Sign up to set email alerts
|

How Do Price and Quantity Promotions Affect Hedonic Purchases? An ERPs Study

Abstract: Due to consuming hedonic products unnecessary to basic well-being, consumers need justifications for pleasure. However, different justifications have differential influences in promoting hedonic purchases, such as price and quantity promotions (PP and QP), the difference being that the latter requires purchasing additional units to get the same discount as the former. In the present study, even-related potentials (ERPs) was applied to reveal the timing of brain activities to further understand how promotion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 54 publications
(79 reference statements)
1
34
0
Order By: Relevance
“…A mismatch between actual and expected stimulus elicits an N2 component at 200-350 ms, implying cognitive control in decision-making processes. In the late cognitive stages, LPP is an effective indicator of motivation and emotional arousal, occurring 300-500 ms after stimulus onset and lasting hundreds of milliseconds (Nieuwenhuis et al, 2005;Liu et al, 2014;Jin et al, 2017;Jing et al, 2019). As in the marketing literature, LPP amplitude was positively correlated with sustaining attention involvement and purchasing motivation (Ma et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…A mismatch between actual and expected stimulus elicits an N2 component at 200-350 ms, implying cognitive control in decision-making processes. In the late cognitive stages, LPP is an effective indicator of motivation and emotional arousal, occurring 300-500 ms after stimulus onset and lasting hundreds of milliseconds (Nieuwenhuis et al, 2005;Liu et al, 2014;Jin et al, 2017;Jing et al, 2019). As in the marketing literature, LPP amplitude was positively correlated with sustaining attention involvement and purchasing motivation (Ma et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…This cognitive function of P2 might contribute to the relationship between purchase intention and variation in attention involvement. The anterior N2 component has also been used to investigate the role of conflict detection (Folstein and Van Petten, 2008;Ma et al, 2010;Liu et al, 2014;Jin et al, 2017;Jing et al, 2019). A mismatch between actual and expected stimulus elicits an N2 component at 200-350 ms, implying cognitive control in decision-making processes.…”
Section: Introductionmentioning
confidence: 99%
“…Our examination gained us a significant main effect of promotion type for the N2 component. Consumer neuroscience studies indicated that the component is positively related to perceptual conflict (e.g., Wang et al, 2016 ; Jing et al, 2019 ). The result for N2 has provided the argument about reaction time with evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A total of (50) images of snacks (i.e., a small meal, like a chocolate bar) as hedonic items whose hedonic score is higher than utilitarian score ( Jing et al, 2019 ) were chosen and manipulated to a similar size, 300 × 300 pixels. As shown in Figure 1 , in order to have enough trials and acceptable signal to noise ratio, the following amounts of discount, 1.5, 2.5, 3.5, 4.5, or 5.5 yuan, and 0 yuan donation was considered as pure price promotion, while 1, 2, 3, 4, or 5 yuan discount and a fixed 0.5 yuan donation was done as a mixed promotion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation